Intrathecal insulin-like growth factor 1 but not insulin enhances myelin repair in young and aged rats. (1st May 2017) - Hlavica, Martin; Delparente, Aro; Good, Andrin; Good, Nicolas; Plattner, Patricia S.; Seyedsadr, Maryam S.; Schwab, Martin E.; Figlewicz, Dianne P.; Ineichen, Benjamin V.
Highlights: Insulin-like growth factor 1 (IGF-1) enhanced remyelination in young and aged rats. Insulin, functionally related to IGF-1, did not enhance remyelination. Aged rats show less pronounced myelin repair compared to young rats. Aged rats are model for chronic demyelination faced in chronic multiple sclerosis. Abstract: One main pathological hallmark of multiple sclerosis (MS) is demyelination. Novel therapies which enhance myelin repair are urgently needed. Insulin and insulin-like growth factor 1 (IGF-1) have strong functional relationships. Here, we addressed the potential capacity of IGF-1 and insulin to enhance remyelination in an animal demyelination model in vivo . We found that chronic intrathecal infusion of IGF-1 enhanced remyelination after lysolecithin-induced demyelination in the spinal cord of young and aged rats. Aged rats showed a weaker innate remyelination capacity and are therefore a good model for progressive MS which is defined by chronic demyelination. In contrast to IGF-1, Insulin had no effect on remyelination in either age group. Our findings highlight the potential use of IGF-1 as remyelinating therapy for MS, particularly the progressive stage in which chronic demyelination is the hallmark.